Preventing Youth Violence: Rethinking the Role of Gender in Schools - Sundaram, Vanita; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Pivot, 2014)
Young people explain, excuse and justify violence in a range of situations and view violence prevention as a difficult, if not impossible, endeavour. But how do young people form these views, and how can this knowledge be used by schools to reduce youth violence? This book explores these questions in a study with British teenagers.
Keywords: Social sciences; Educational sociology; Gender identity in education; Juvenile delinquents; Sociology; Education and sociology; Sociology, Educational; Childhood; Adolescence; Social groups; Sex (Psychology).; Gender expression; Gender identity; Social Sciences; Gender Studies; Youth Offending and Juvenile Justice; Gender and Education; Childhood, Adolescence and Society; Sociology of Education; Sociology of Education